A new species and a new record of the genus Acalypta (Hemiptera: Heteroptera: Tingidae) from Japan - Souma, Jun (Zootaxa, 2019)
Two moss-feeding species of the lace bug genus Acalypta Westwood, 1840 (Hemiptera: Heteroptera: Tingidae), are reported from Japan. Acalypta cooleyi Drake, 1917, is recorded for the first time from Japan (Honshu), and a new species, A. pallidicoronata sp. nov., is described from Tsushima Island.